Google Images as a photographic archive of the armed conflict in Colombia - Silva, Manuel (Meridional. Revista Chilena de Estudios Latinoamericanos, 2019)
In this article, the Internet search engine Google images is analyzed as a photographic archive and it is proposed that this tool constitutes a visual field of the armed conflict in Colombia. Therefore, the text outlines the assumptions that support this characterization, recognizes the particularity of Google images as a archive and describes and analyzes part of its content. The article involves questions as like: can we find continuities and/or discontinuities in the photographic images of Colombian’s armed conflict accessible in Google searches? If so, what kind or nature are they? What can be, in consequence, the characteristics of the Google image search engine if it is considered as a visual archive of the armed conflict experienced in Colombia? Finally, the text offers two conclusions. Following Foucault, it points out that this virtual archive can be read as a regulator of the visible and memorable of war. And, following Rancière, it suggests that this visual archive constitutes one more operation of the partition of the sensible